Connections on Bundles (Dhaka University Journal of Science, 2012)
This paper is a survey of the basic theory of connection on bundles. A connection on tangent bundle TM, is called an affine connection on an m-dimensional smooth manifold M. By the general discussion of affine connection on vector bundles that necessarily exists on M which is compatible with tensors.DOI: http://dx.doi.org/10.3329/dujs.v60i2.11492 Dhaka Univ. J. Sci. 60(2): 191-194, 2012 (July)